Lets say that the two unknown integers are [tex]n[/tex] and [tex]m[/tex].
We know the following things about [tex]n[/tex] and [tex]m[/tex]:
[tex]n+m=26[/tex]
[tex]n^2+m^2=340[/tex]
And, we want to find [tex]nm[/tex].
To solve this, we'll use the expansion of the squared of the sum of any two inegers; this is expressed as:
[tex](n+m)^2=n^2+2nm+m^2[/tex]
So, given what we know about the unknown integers, the previous can be written as:
[tex](26)^2=340+2nm[/tex]
We can easily solve for [tex]nm[/tex]:
[tex]nm= \frac{(26)^2-340}{2}= \frac{676-340}{2}= \frac{336}{2}=168 [/tex]
The answer is 168.
Another approach to solve the problem is, from the two starting equations, compute the values of [tex]n[/tex] and [tex]m[/tex], which are 12 and 14, and directly compute their product; however, the approach described is more elegant.